2015
DOI: 10.28945/2298
|View full text |Cite
|
Sign up to set email alerts
|

Educational Technology: A Review of the Integration, Resources, and Effectiveness of Technology in K-12 Classrooms

Abstract: There is no questioning that the way people live, interact, communicate, and conduct business is undergoing a profound, rapid change. This change is often referred to as the "digital revolution," which is the advancement of technology from analog, electronic and mechanical tools to the digital tools available today. Moreover, technology has begun to change education, affecting how students acquire the skill sets needed to prepare for college and a career and how educators integrate digital technological instru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(72 citation statements)
references
References 40 publications
2
66
0
4
Order By: Relevance
“…Strong management concerns indicate an intense concern with the logistical aspects of LMS implementation. Examples of logistical concerns that are mostly related to technology integration in education include proper infrastructural support, free time, and access to and use of suitable resources (Ocak, 2011;Delgado, Wardlow, McKnight, & O'Malley, 2015). Such concerns can be explained by the lack of training, where the majority of the participants (87%; n=41) had not receive training regarding the use of LMS.…”
Section: Resultsmentioning
confidence: 99%
“…Strong management concerns indicate an intense concern with the logistical aspects of LMS implementation. Examples of logistical concerns that are mostly related to technology integration in education include proper infrastructural support, free time, and access to and use of suitable resources (Ocak, 2011;Delgado, Wardlow, McKnight, & O'Malley, 2015). Such concerns can be explained by the lack of training, where the majority of the participants (87%; n=41) had not receive training regarding the use of LMS.…”
Section: Resultsmentioning
confidence: 99%
“…Repeatedly producing research that does not answer essential questions is a waste of researcher time and resources. For example, it has been difficult to determine the effectiveness of integration of instructional technology in the classroom because of variance in commitment to learning new teaching methods (Delgado, Wardlow, McKnight, & O'Malley, 2015;Nicol, Owens, Le Coze, MacIntyre, & Eastwood, 2018). Researchers can collaborate ahead of time to define sufficient level of fidelity and how fidelity can best be measured.…”
Section: Preregistered Adversarial Collaborationsmentioning
confidence: 99%
“…The importance of contextual factors in the effectiveness of CAI was discussed in a review by Delgado et al (2015), who identified different ways of integrating technology in schools. They distinguished between the use of technology to replace teaching on the one hand, and blended learning on the other hand; in the latter, device-driven and face-to-face teaching are combined in different ways depending on the aims of the school, the capabilities of the teachers and pupils, and institutional factors, such as availability of resources.…”
Section: Contextual Factors In the Implementation Processmentioning
confidence: 99%